Historical biogeography of a species rich plant genus from the montane forests of the tropical Andes, "Macrocarpaea" (Gentianaceae) - Vieu, Julien (Neuchâtel, 2015)
Differences in species diversity among regions and among taxa have long fascinated evolutionary biologists, but the mechanisms that generated these patterns remain insufficiently understood. The middle elevation montane forests of the tropical Andes (MMF) stand out as the region of the world harbouring the highest level of both species diversity and endemism which make this region an appropriate place to address mechanisms that favour high species diversity. The main goal of this thesis was to test whether the high plant diversity of the MMF was the result of the slow accumulation of species or through episodes of rapid diversification. Additionally this thesis investigated the contribution of geographical processes such as dispersal and allopatric speciation vs. adaptive processes such as ecological speciation to the diversification of plants in the region. We used the plant genus Macrocarpaea (Gentianaceae) as a study system to tackle these questions. Macrocarpaea occurs in most montane regions of the Neotropics but its diversity (96 species) is within the MMF, suggesting that the genus radiated in the region. Also, the genus has a broad altitudinal distribution (500-3500m) but most species have a much narrower altitudinal range indicating that adaptive divergence along elevation gradients might have been common.
We first reconstructed a dated phylogenetic hypothesis that we subsequently used to infer the historical biogeography of the genus and to estimate diversification rates through time and among lineages. We found a pattern of diversification consistent with the signature of a radiation for Macrocarpaea in the Andean MMF. The radiation coincides with a period of rapid colonisation and range expansion across the entire extant distribution of the genus in the Andes starting some 7.2 million years ago. Furthermore, analyses support allopatric founder-event speciation as the dominant process contributing to the geographic and phylogenetic structure of the genus. We suggest that the likely rapid establishment of the MMF in the late Miocene when the Andes attained critical elevation to modify regional climates, provided large new areas of suitable habitat for Macrocarpaea to quickly colonise through repeated founder-events. This wave of colonisation triggered rapid diversification and as the range of the MMF became progressively occupied, the diversification rate slowed.
Then we investigated the contribution of adaptive divergence and niche conservatism in this radiation. We used morphological and climatic data in a phylogenetic comparative method framework to compare a set of evolutionary scenarios of various levels of complexity. We showed that the hypothesis of an adaptive radiation for Macrocarpaea in the MMF is very unlikely. The genus has remained confined to the upper montane forests (UMF>1800m) during more than the half of its history possibly due to evolutionary constraints. Later, and coincidental with the beginning of the Pleistocene climatic oscillations, a derived clade, the micrantha alliance, successfully colonized and radiated in the lower montane forests (LMF<1800m). This colonisation has been accompanied by the evolution of a new leaf phenotype unique to the species of the micrantha alliance that likely represents adaptation to life in this new adaptive zone. Therefore, our results suggested that niche conservatism and geographical processes have dominated most of the diversification history of Macrocarpaea, but that a rare adaptive divergence event allowed a transition into a new adaptive zone and enabled a second subsequent radiation in this zone through geographical processes.
Finally, we investigated the potential impact of the Pleistocene climatic oscillation (PCO) on the population structure in lower montane forest species. We used amplified fragment length polymorphism molecular makers (AFLP’s) to investigate the phylogeography of 12 species in the micrantha alliance. We showed that some species identified on the basis of cryptically morphological differences, displayed complex and potentially reticulated relationships, requiring further examination. We also showed that populations of a species endemic to a single valley connected to the dry system of the Rio Marañón in northern Peru have low levels of gene diversity. We suggested that this is due to a recent demographic bottleneck resulting from the contraction of the montane wet forests into refugia as consequence of the expansion of the dry system into the valley during the glacial cycles of the PCO. This hypothesis needs further study, but its confirmation would imply that different valleys of the Andes might have responded in very different manners to the PCO.
, Doctorat, Université de Neuchâtel, Institut de biologie
Keywords: Andes; biogéographie; diversification; phylogénie; plantes; Andes; biogeography; diversification; phylogeny; plants